Effectiveness of Virgin Coconut Oil (VCO) Topically to The Formation Granulations of Grade I and II Pressure wound (Decubitus) - Onggang, Fransiskus Salesius; Batbual, Bringiwatty; Romana, Aben; Mau, Amelianus (Ahmar Metastasis Health Journal, 2024)
Decubitus ulcers or pressure sores are local tissue necrosis when soft tissue is compressed between the bony prominences and the external surface for a long period of time, due to pressure or due to frictional forces. Virgin Coconut Oil (VCO) is pure coconut oil produced from the processing of coconut meat without heating or through low-temperature heating, thus producing oil with a clear color and free from free radicals due to heating. This research aims to determine the effectiveness of using Virgin Coconut Oil (VCO) topically to treat pressure sores (decubitus) grade I and II.  The research method used in quantitative research is quasi-experimental with a one-group pre-test and post-test design. Population study This is respondents who experienced wound press decubitus because of prolonged bed rest with condition decubitus wounds grade 1 and 2. Intervention study on group treatment with give virgin coconut oil with a temperature 37 degrees Celsius with method oil done light massage of the back (3 ml), sacrum (1 ml), heel (0.5 ml), buttocks (1.5 ml), ischium (1 ml), elbow (1 ml), malleolus (1 ml) and trochanter (1 ml) for approximately 5 minutes with frequency twice a day during seven days. The results study showing from treatments 1, II, III, IV, V , VI, and VII show results significant exists growth granulation grade II decubitus tissue. Wilcoxon Test showing There is an influence of CVO on growth network granulation on decubitus injury Grade 2. The conclusion is Virgin Coconut Oil is effective in the growth process grade II decubitus granulations. It is recommended that future studies explore the use of technologies, such as laser or ultrasound therapy, along with topical application of VCO to see if there is an improvement in the speed and quality of pressure sore healing.